ANTIOXIDANT, ANTI-INFLAMMATORY AND ANTIMICROBIAL ACTIVITY OF WHOLE PLANT OF ALLMANIA NODIFLORA ( L) R. BR EX WIGHT: Pharmaceutical Sciences-Pharmacy - PADMAJA, KOTA; GANAPATY, SERU; PANDA, JAGADEESH; SULAKSHNA, MARY; SHEIK, AASHIA; PATEL, BHAVIKA; ROJA, MONISHA; BHAVYA (International Journal of Life Science and Pharma Research, 2017)
Allmania nodiflora (L) R. Br. ex wight is a small herb belongs to Amaranthaceae family and is green leafy vegetable, used as folk medicine to treat constipation, decentry and febrifuge contains adequate amount of nutrients. The ethanolic extract (EEAN) of whole plant was chosen to investigate anti oxidant, antimicrobial and anti-inflammatory activity. The extract shows significant antioxidant activity evaluated by DPPH assay, Superoxide Radical and Hydroxyl radical scavenging activity compared with that of standard (ascorbic acid) and antimicrobial activity was evaluated against clinically important bacterial and fungal strains using cup plate method. Anti inflammatory activity was evaluated by Carrageenan induced rat paw edema method by the oral administration of EEAN (100, 250 mg/kg) exhibited significant and dose dependant antiinflammatory activity.